2011
DOI: 10.1249/mss.0b013e3182118891
|View full text |Cite
|
Sign up to set email alerts
|

A 45-Minute Vigorous Exercise Bout Increases Metabolic Rate for 14 Hours

Abstract: In young male subjects, vigorous exercise for 45 min resulted in a significant elevation in postexercise energy expenditure that persisted for 14 h. The 190 kcal expended after exercise above resting levels represented an additional 37% to the net energy expended during the 45-min cycling bout. The magnitude and duration of increased energy expenditure after a 45-min bout of vigorous exercise may have implications for weight loss and management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 29 publications
4
30
0
Order By: Relevance
“…This finding is congruent with other studies which have examined the effects of HIT on EPOC and reported small changes in postexercise EE (Chan & Burns 2013;Williams et al 2013;LaForgia et al 1997) but at odds with a recent report which described a large increase in post-exercise EE after an acute bout of continuous moderate intensity cycling (Knab et al 2011). This latter investigation is noteworth gi en the gold standard ethodolog e plo ed.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…This finding is congruent with other studies which have examined the effects of HIT on EPOC and reported small changes in postexercise EE (Chan & Burns 2013;Williams et al 2013;LaForgia et al 1997) but at odds with a recent report which described a large increase in post-exercise EE after an acute bout of continuous moderate intensity cycling (Knab et al 2011). This latter investigation is noteworth gi en the gold standard ethodolog e plo ed.…”
Section: Discussionsupporting
confidence: 85%
“…Closer scrutiny of the study protocol however reveals one key difference between study methodologies. Notably, in the study conducted by Knab et al (2011) participants were fed back the energy which they expended during exercise (2171 kJ) so that they consumed a much greater amount of food on the exercise trial than their control trial. This extra energy would have significantly augmented resting metabolism (thermic effect of feeding) above that on the control trial and therefore the EPOC that the researchers reported reflects the true increase with exercise plus the increase promoted by a heightened food intake.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although differential measurement error is possible, our results suggest that a higher proportion of vigorous physical activity within each category of total physical activity was associated with less adiposity. Given the same energy expenditure, high-intensity exercise may stimulate greater fat oxidation and oxygen consumption during the postexercise period [27,28].…”
Section: Benefit Of Higher Exercise Intensity On Abdominal Fat Loss [mentioning
confidence: 99%
“…It is an open-circuit, pull-type, whole-room indirect calorimeter built with walk-in cooler panels [14]. This chamber and the reproducibility of the data generated has been previously described [15]. EE was calculated using an abbreviated Weir's formula (VO 2 X 3.941) + (VCO 2 X 1.106), where VO 2 is the volume of oxygen consumed (L/minute) and VCO 2 is the volume of carbon dioxide released (L/minute).…”
Section: Study Participantsmentioning
confidence: 99%